Progress in the design of nanoporous adsorbent materials containing transition metals for the removal of contaminants of emerging concern. Issue 1 (1st January 2021) - Muñoz-Senmache, Juan C.; Fernández-Reyes, Bethzaely; Hernández-Maldonado, Arturo J.
ABSTRACT: Significant attention has been paid to contaminants of emerging concern (CECs) for several years due to their persistence in water sources and toxicity. The necessity of upgrading current wastewater treatment technologies is vital to guarantee timely remediation of CECs, particularly given the scarcity of potable water for direct human consumption and even for agricultural irrigation. In this regard, the integration of transition metals onto porous adsorbent materials for use in water and wastewater treatment operations could play a significant role due to their ability to undergo specific interactions (i.e., complexation-type) with CECs at ambient temperature. Furthermore, coupling these interactions with hydrophobicity inducing species or phases in situ (i.e. hierarchically) further enhances affinity and capacity toward CECs. This review highlights the progress so far in the bench-scale design of transition metal-based nanoporous adsorbents, including hierarchical composites prepared via confined space synthesis, for the removal of CECs from water at ambient conditions.